Cross-sectional networks of depressive symptoms before and after antidepressant medication treatment - Bos, Fionneke M.; Fried, Eiko I.; Hollon, Steven D.; Bringmann, Laura F.; Dimidjian, Sona; DeRubeis, Robert J.; Bockting, Claudi L. H. (Social Psychiatry and Psychiatric Epidemiology: The International Journal for Research in Social and Genetic Epidemiology and Mental Health Services, 2018)
Purpose: Recent reviews have questioned the efficacy of selective serotonin reuptake inhibitors (SSRIs) above placebo response, and their working mechanisms remain unclear. New approaches to understanding the effects of SSRIs are necessary to enhance their efficacy. The aim of this study was to explore the possibilities of using cross-sectional network analysis to increase our understanding of symptom connectivity before and after SSRI treatment. Methods: In two randomized controlled trials (total N = 178), we estimated Gaussian graphical models among 20 symptoms of the Beck Depression Inventory-II before and after 8 weeks of treatment with the SSRI paroxetine. Networks were compared on connectivity, community structure, predictability (proportion explained variance), and strength centrality (i.e., connectedness to other symptoms in the network). Results: Symptom severity for all individual BDI-II symptoms significantly decreased over 8 weeks of SSRI treatment, whereas interconnectivity and predictability of the symptoms significantly increased. At baseline, three communities were detected; five communities were detected at week 8. Conclusions: Findings suggest the effects of SSRIs can be studied using the network approach. The increased connectivity, predictability, and communities at week 8 may be explained by the decrease in depressive symptoms rather than specific effects of SSRIs. Future studies with larger samples and placebo controls are needed to offer insight into the effects of SSRIs. (PsycINFO Database Record (c) 2019 APA, all rights reserved)
Keywords: Adult; Antidepressant Drugs; Antidepressant treatment; Cross-Sectional Studies; Data Interpretation, Statistical; Depressive Disorder, Major; Female; Gaussian graphical models (GGM); Humans; Major Depression; Major depressive disorder; Male; Middle Aged; Models, Theoretical; Network analysis; Outcome Assessment (Health Care); Paroxetine; Selective serotonin reuptake inhibitors; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Symptoms